FMEA-Based Risk Mitigation Strategy for Preventing Final Drive Component Failures in Bulldozers - Sutrisna, Sutrisna (ReTII, 2025)
Failures in bulldozer final drive components are among the leading causes of increased downtime and maintenance costs in heavy equipment operations, particularly in mining and construction sectors. This study aims to analyze the potential failure risks of final drive components and to formulate effective risk mitigation strategies using the Failure Mode and Effects Analysis (FMEA) method. Data were collected through field observations, interviews with maintenance technicians, and analysis of historical failure records and Scheduled Oil Sampling (SOS) results. Each failure mode was evaluated based on three main parameters: Severity (S), Occurrence (O), and Detection (D), to determine the Risk Priority Number (RPN). The results indicate that failures in bearing and seal oil components have the highest RPN values 270, making them the primary focus of mitigation. Proposed strategies include increasing inspection frequency, improving lubrication quality control, and implementing condition-based maintenance systems. The application of these mitigation strategies is expected to reduce the likelihood of component failures and enhance the reliability of the bulldozer final drive system